Sinergitas Ilmu Dan Adab Dalam Perspektif Islam - Tahir, Gustia (Jurnal Adabiyah, 2015)
Science and letters are two interconnected words. It can be seen from the position of human being who were bestowed by God with commonsense and brain and the very honorable position as caliph. Human being with his thought can produce scienceÂ  and thus become scientist, and with his science he can also create civilization. Therefore, through science and litters, human being can develop his potency as caliph both physically and spiritually. All this potency must be actualized to be a power and commitment for the welfare of mankind to promote the civilization. It mean that civilization can be established just by those of noble characters. This writing is to try to explore and elaborate the sinergity between science and letters in Islamic perspective. It aims at describing in detail how formerly Islam highly appreciate the science and literature.